Understanding terrorism : challenges, perspectives, and issues - Martin, Gus (Los Angeles : SAGE, 2021)
"Understanding Terrorism: Challenges, Perspectives, and Issues offers a multidisciplinary, comprehensive exploration of domestic and international terrorism that helps students develop the knowledge and skills needed to critically assess the expressions and underlying causes of terrorism. The author explains theory and provides in-depth analysis in an accessible, engaging manner that helps readers develop the knowledge and skills they need. KEY FEATURES: Opening Viewpoints: At the beginning of each chapter, these boxes present relevant examples of theories and themes that will be discussed in the following chapter-grabbing readers' attention and drawing them into the material. Chapter in Perspective: Chapters incorporate focused presentations in special interest boxes that explore people, events, organizations, and movements that are relevant to the chapter. Discussion Boxes: Each chapter concludes with discussion boxes that highlight controversial issues and pose challenging questions to stimulate critical thinking and debate. Wide-ranging Illustration Program: A variety of photos, charts, graphs, and maps help students appreciate and understand the events and people covered in the book. NEW TO THIS EDITION:"--
Includes bibliographical references (pages 521-541)
Keywords: Terrorism